The nutritional biochemistry of chromium (III) - Vincent, John B. (John Bertram) (Elsevier, 2007)
Chromium nutritional supplements are the second best selling mineral supplements after calcium as chromium is found in pills, sports drinks, chewing gums, smoothies, and numerous other products. Chromium has been promoted to promote weight loss and muscle development and most recently to be available to treat the symptoms of type 2 diabetes and related conditions. The aim of The Nutritional Biochemistry of Chromium(III) is to examine the four most controversial areas of chromium nutrition and biochemistry: - is chromium an essential element for humans and are chromium nutritional supplements of value? - what biochemical role, if any, does chromium play in the body - can large doses of chromium(III) be used to treat symptoms of type 2 diabetes, cardiovascular disease, and related medical conditions - is the use of chromium(III) supplements a health concern. Scientific experts, who are recognized leaders in the field, weigh in with their opinions on both sides of these issues in this book. A background review of the field from 1955-1995 by Vincent opens the book and concludes with a summary by Dr. Forrest Nielsen, Center Director of the USDA's Grand Forks Human Nutrition Research Center concludes the book. * Point-counterpoint format, providing both sides of major issues * Complete coverage of current issues, including nutrition, health, biochemical role and toxicology * Authors are recognised experts and leaders in this field.